Social Protection in a Crisis : Argentina's Plan Jefes y Jefas - Galasso, Emanuela; Ravallion, Martin (Washington, DC: World Bank, 2014)
The article assesses the impact of Argentina's main social policy response to the severe economic crisis of 2002. The program was intended to provide direct income support for families with dependent sand whose head had become unemployed because of the crisis. Counter factual comparisons are based on a matched subset of applicants not yet receiving program assistance. Panel data spanning the crisis are also used. The program reduced aggregate unemployment, though it attracted as many people into the workforce from inactivity as it did people who otherwise would have been unemployed. Although there was substantial leakage to formally ineligible families and incomplete coverage of those who were eligible, the program did partially compensate many losers from the crisis and reduced extreme poverty.